Microbial evolution under extreme conditions - Bakermans, Corien, 1971- (Life in extreme environments., 2014)
This book explores the current state of knowledge about microbial evolution under extreme conditions addressing questions from the perspectives of different extreme environments, organisms, and evolutionary processes: What is known about the processes of evolution that produce adaptations to extreme conditions? Can this knowledge be applied to other systems? What requires future research?